Aseptic versus Sterile Acellular Dermal Matrices in Breast Reconstruction: An Updated Review - Lyons, Daniel A. (Plast Reconstr Surg Glob Open, 2016)
BACKGROUND: As the use of acellular dermal matrices in breast reconstruction has become more commonplace and efforts are made to improve on postoperative outcomes, the method of acellular dermal matrix (ADM) processing (aseptic versus sterile) has become a subject of interest. This article provides an updated overview of the critical aspects of ADM processing in addition to application of ADMs in single- and two-stage breast reconstruction, a review of the morbidity associated with ADM use, and alternatives. METHODS: A literature review was performed in PubMed identifying recent systematic reviews, meta-analyses, and head-to-head comparisons on aseptically processed ADM and sterile-processed ADM in implant-based breast reconstruction. RESULTS: Recent meta-analyses have shown a 2- to 3-fold increase in infections and tissue expander/implant explantation rates and a 3- to 4-fold increase in seroma formation compared with non-ADM reconstruction techniques. Comparisons of aseptic and sterile ADMs in multiple studies have shown no significant difference in infection rates and equivocal findings for other specific complications such as seroma formation. CONCLUSIONS: Current evidence on the impact of processing techniques that improve ADM sterility on postoperative morbidity in implant breast reconstruction is unclear. Deficiencies of the available data highlight the need for well-designed, multicenter, randomized controlled studies that will aid in optimizing outcomes in implant-based breast reconstruction.